Molecular structure, stability and spectroscopic properties of verteporfin and its derivatives – A theoretical insight - Raju Suresh Kumar; Abdulrahman I. Almansour; Natarajan Arumugam; Khloud Ibrahim Al-Shemaimari; Sakkarapalayam M. Mahalingam; Sakkarapalayam Murugesan Senthil Kumar (Journal of King Saud University: Science, 2024)
The electronic and geometrical structure of the well-known photosensitizer verteporfin VD (1), as well as its guanidine and dicarboxylic acid derivatives VD(Gua)1 (2), VD(COOH)2 (3), and VD(Gua)3 (4) are analyzed using density functional theory (DFT) calculations. The investigation of compound’s thermal and kinetic stability supports their potential use as photodynamic therapeutics. Though there are reports about the biological applications of verteporfin and its derivatives, the basic structural futures at molecular level which play a crucial role in their potential applications, are not well-explored. The results of electronic and spectral analyses by DFT calculation in this work reveal important points underlying the applications of these compounds.